Influence of cooperative learning and participation on biological learning achievement - Hesmi Rema Dwita; Bambang Sahono (UNIB Press, 2019)
The objective is to know to Influence of cooperative learning and participation on biological learning achievement. The research method is a quation experiment with the experimental design used by the research with 2x2 factorial design. Research subject of X1 IPA class X1 IPA 1 as experimental class that applied to implementation of cooperative learning model of STAD type while X1 IPA 2 class is used as experimental class II while XI IPA 3 is not subject to sample action in This research is all students of the grade XI IPA 1, XI IPA 2 and XI IPA 3 which are divided into 3 classes. Data analysis is done with the average (class) and test- Anava. The results of this study show: 1) There are differences in learning outcomes of students who learn with cooperative learning models of STAD and JIGSAW, 2) There is a influence of interaction between cooperative learning models and participation in learning outcomes Students, 3) There are differences in the learning outcomes of students whose study participation is learning with the cooperative learning models of STAD and JIGSAW, 4) There are differences in the learning outcomes of students who study the low learning with models The cooperative learning of STAD and JIGSAW types